Effect of the Eight-Week Sand Surface Exercise, Water Surface Exercise, and Power Leg Muscles Training Methods Toward Agility of Basketball Players for Adolescent Players - Muhammad Irvan Eva Salafi; Wawan Sundawan Suherman; Bernadeta Suhartini; Muhammad Sigit Antoni; Kukuh Wahyudin Pratama (OVS LLC, 2022)
Study purpose. Agility plays an essential role in basketball so increased agility needs to be a concern in the physical conditioning exercises of basketball players. To achieve the best results possible with an exercise, the type and manner of the exercise must be considered. The more varied is the training model offered to athletes, the more will it further encourage athletes not to feel exhausted while training. However, the training model used is still limited to hard textured courts. Though the use of textured fields such as water and sand has an impact other than power load, it lowers the rate of injury. Materials and methods. The method used in this study was a 2 x 2 factorial design experiment. This study involved 36 men's basketball athletes ages 16-18. The leg power instrument used a vertical jump, agility assessment used an agility test, and analysis of this study data used the ANOVA test. Results. (1) the sand exercise method shows higher results than the water exercise method; (2) athletes who have high limb power are better in agility testing than athletes who have low limb power; and (3) there is an interaction of water exercise and sand exercise methods and power of the limbs against agility. Conclusions. The results of this study could prove that sand exercise methods are more effectively used in increasing agility to be an alternative for coaches.